2015
DOI: 10.1371/journal.pone.0134103
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Provides New Insights in Phosphorus Homeostasis Subjected to Pi (Inorganic Phosphate) Starvation in Tomato Plants (Solanum lycopersicum L.)

Abstract: Phosphorus is a major nutrient acquired by plants via high-affinity inorganic phosphate (Pi) transporters. To determine the adaptation and homeostasis strategy to Pi starvation, we compared the proteome analysis of tomato leaves that were treated with and without Pi (as KH2PO4) for 10 days. Among 600 reproducible proteins on 2-DE gels 46 of them were differentially expressed. These proteins were involved in major metabolic pathways, including photosynthesis, transcriptional/translational regulations, carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 63 publications
1
25
0
1
Order By: Relevance
“…Recent genomic and proteomic studies with the model plant Arabidopsis thaliana argue that there is programmed down-regulation of gene expression for photosynthesis under P starvation, with simultaneous up-regulation of genes encoding photoprotective measures and systemsscavenging reactive oxygen species (Misson et al 2005;Morcuende et al 2007;Wu et al 2003). Similar results have been found in other herbaceous species, including maize (Zhang et al 2014), tomato (Muneer and Jeong 2015), and rice (Park et al 2012).…”
Section: Photosynthesissupporting
confidence: 54%
See 1 more Smart Citation
“…Recent genomic and proteomic studies with the model plant Arabidopsis thaliana argue that there is programmed down-regulation of gene expression for photosynthesis under P starvation, with simultaneous up-regulation of genes encoding photoprotective measures and systemsscavenging reactive oxygen species (Misson et al 2005;Morcuende et al 2007;Wu et al 2003). Similar results have been found in other herbaceous species, including maize (Zhang et al 2014), tomato (Muneer and Jeong 2015), and rice (Park et al 2012).…”
Section: Photosynthesissupporting
confidence: 54%
“…Numerous studies suggest that native Australian plants with specialized root systems can tolerate reduced soil phosphorus availability (Lambers et al 2012;Sulpice et al 2014), and that plants exhibit strong short-term responses to P stress (Muneer and Jeong 2015;Zhang et al 2014). Our field-based study is unique in considering the chemical and physiological adaptations of generalist plants (i.e., without specialized root structures) of a variety of life forms to longterm limitation of P supply.…”
Section: Discussionmentioning
confidence: 99%
“…As result, the grain yield or production of crops was compromised by P deficiency [ 9 , 17 , 18 ]. Short-term P deprivation not only reduced P concentration but also decreased the total chlorophyll (Chl) and carotenoid content in tomato seedlings [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the root parts, low P triggers a set of shoot traits under both vegetative and reproductive stages, including dark-green or purple leaves due to anthocyanin accumulation, reduced leaf area and leaf numbers, and less final production. In tomato, proteomic analysis revealed that scavenging of reactive oxygen species (ROS) was induced to cope with low P content in the leaves [ 4 ]. Low phosphate reduces photosynthetic pigments and disturbs all the processes of in the photosynthetic machinery [ 5 ], as well as changes to primary carbon metabolism and other primary and secondary metabolism pathways [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%